Q) Solve the following quadratic equations by factorization method:

4\sqrt{3}x^2 + 5x - 2\sqrt{3} = 0


4\sqrt{3}x^2 + 5x - 2\sqrt{3} = 0

4\sqrt{3} x^2 +8x -3x -2\sqrt{3}=0

4x(\sqrt{3} x+2) -\sqrt{3}(\sqrt{3}x +2) =0

(\sqrt{3}x +2)(4x -\sqrt{3}) =0

(\sqrt{3}x +2)=0\implies x=-\frac{2}{\sqrt{3}}


(4x -\sqrt{3}) =0\implies x=\frac{\sqrt{3}}{4}

Please do press “Heart” button if you liked the solution. 

Leave a Comment

Your email address will not be published. Required fields are marked *

Scroll to Top